Combining Student Teams Achievement Divisions (STAD) and Talking Stick on Learning Achievement of Senior High School - Anggraini, Diah Ayu Febri; Sapir, Sapir (Unversitas Negeri Malang, 2018)
The purpose of this study aims to understand the application of cooperative learning techniques STAD method in collaboration with Talking Stick to improving student learning result of an economics class in Senior High School. This type of research is Classroom Action Research with a qualitative approach. This research consists of two cycles, each cycle consists of four stages of action planning, implementation, observation and reflection. The results showed that the application of cooperative learning techniques STAD method in collaboration with Talking Stick on economic subjects can improve student learning results in economics class. In more detail, in the first cycle, the average pre-test score was about 43.63 and post-test 79.37 with the completeness s percentage 56.25 percent. Meanwhile, in the second cycle, the average value of pre-test value 52.72 with the completeness percentage approximately 6.06% and the post-test score was 84.24 with a completion percentage of 81.81%.